Quantum-Enhanced Magnetic Induction Tomography for Spatial Resolution and Sensitivity Improvements in Non-Invasive Medical Imaging - Abdul Jabbar Lubis; Rachmat Aulia; T. Mohd Diansyah; N. F. Mohd Nasir; Z Zakaria; Aqsha Adity Daulay (Journal of Information Systems and Technology Research, 2025)
Traditional Magnetic Induction Tomography (MIT) systems demonstrate limited spatial resolution and detection sensitivity when analyzing complex conductivity distributions in biological tissues. This research investigates the integration of Nitrogen-Vacancy (NV) centers in diamond substrates to overcome these fundamental limitations. The primary objectives include: (1) developing a quantum-enhanced MIT system with superior magnetic field detection capabilities, (2) quantifying performance improvements in spatial resolution and sensitivity compared to conventional approaches, (3) validating system effectiveness through controlled phantom studies and biological tissue analysis, and (4) establishing technological foundations for next-generation medical imaging applications. This study presents the first comprehensive implementation of quantum sensing technology in tomographic imaging applications. Novel contributions include: development of an integrated NV-center based magnetic field detection system, achievement of 0.8 mm minimum detectable feature size representing 3.5-fold resolution enhancement, demonstration of 0.01 S/m conductivity detection threshold showing 10-fold sensitivity improvement, and validation of 62% reconstruction error reduction with 28% structural similarity enhancement. The quantum-enhanced approach establishes new paradigms for early disease detection and precision medicine applications, providing unprecedented imaging capabilities for medical diagnostics, material characterization, and geophysical exploration. Results demonstrate transformative potential for clinical implementation with 95% sensitivity and 92% specificity in detecting sub-millimeter tissue anomalies